PENINGKATAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA MATERI PERSAMAAN DAN PERTIDAKSAMAAN IRASIONAL MELALUI PENERAPAN MODEL PEMBELAJARAN THE POWER OF TWO SISWA KELAS X MIA 2 SMAN 1 BUKIT SEMESTER 1 TAHUN PELAJARAN 2019/2020 - Ainal Mardiah (Intersections, 2022)
This research is an attempt to increase students' motivation and learning outcomes using The Power of Two method. The type of research is classroom action research (Classroom Action Research). Subjects totaled 22 students. Data collection was carried out using observation, test and documentation techniques. The data validation in this action research is democratic, process, and dialogic validity. The data obtained were analyzed descriptively. The results showed that learning motivation increased from 7 students (31.82%) in the initial condition to 54.55% or 12 students in the first cycle and 20 or 90.91% in the last cycle. The explanation of mastery learning before the improvement of learning is 22.73% or 5 students, increased in the first cycle 12 students or 54.55% and in the last cycle to 19 students or 86.36% with an average value of learning outcomes of 63 .18 to 73.18 and in the last cycle to 82.73